Budaya Organisasi Dalam Mengelola Bisnis Pembiayaan Pada Bank Syariah - Muhammad Lathief Ilhamy Nst (HUMAN FALAH: Jurnal Studi Ekonomi dan Bisnis Islam, 2017)
In the financing process should be run in accordance with established procedures. That's because the financing facilities provided by banks to customers should benefit both. Financing facility should provide benefits to customers gifts in fulfillment of its financing needs at the time that is required to refund some time later. On the other hand, the financing facility should also provide benefits to the bank in the form of shared revenues and margins or other revenue. Most of the revenue is the right of other customers, ie customers who invest their money in the bank get the results or fee in the contract wadiah of funds invested or deposited by the customer.